THE DEVELOPMENT AND ACCEPTANCE OF GENDER-NEUTRAL LANGUAGE IN ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the development and acceptance of gender-neutral language in English, focusing on its linguistic, cultural, and social implications. Over time, the English language has evolved to reduce gender bias, leading to changes in pronouns, job titles, and everyday expressions. The paper examines historical perspectives, the influence of social movements, and the role of institutions in promoting gender-neutral language. Additionally, it highlights the challenges of implementing such changes and the varying degrees of acceptance in different communities.